Digital Flipbook-Based Learning Media Design in Integrated Thematic Learning on the Theme of Growth and Development of Living Things in Class III Inclusive Elementary School - Zen, Ahmad Muzakki; Muhith, Abd; Wahono, Suparwoto Sapto (Fakultas Agama Islam Universitas Ibn Khaldun Bogor, 2024)
AbstrakPenelitian ini bertujuan untuk mengatasi kesulitan pemahaman siswa kelas III Inklusif di SD Al-Irsyad Al-Islamiyah Jember dalam pembelajaran tematik tema pertumbuhan dan perkembangan makhluk hidup. Data dari 25 siswa menunjukkan bahwa 80% mengalami kesulitan dengan metode konvensional, sedangkan 90% membutuhkan inovasi, khususnya media berbasis flipbook digital. Sebanyak 85% siswa menyukai media digital, dan 83% tertarik pada ilustrasi menarik. Lebih dari 90% setuju dengan pengembangan Flipbook Digital sebagai media pembelajaran.Penelitian ini menggunakan metode penelitian dan pengembangan ADDIE, dengan instrumen validasi dan angket respon siswa. Analisis data melibatkan penilaian ahli, persentase hasil angket, dan desain one-group pretest posttest. Hasil penelitian diharapkan dapat memberikan kontribusi terhadap peningkatan pemahaman siswa kelas III Inklusif terhadap tema pertumbuhan dan perkembangan makhluk hidup melalui media pembelajaran berbasis flipbook digital.Kata kunci: Flipbook Digital, Media, Pembelajaran Tematik Terpadu Abstract This study aims to overcome the difficulty of understanding class III Inclusive students at Al-Irsyad Al-Islamiyah Jember Elementary School in thematic learning on the theme of growth and development of living things. Data from 25 students showed that 80% had difficulty with conventional methods, while 90% needed innovation, especially digital flipbook-based media. As many as 85% of students like digital media, and 83% are interested in interesting illustrations. More than 90% agreed with the development of Digital Flipbooks as learning media. This study used the ADDIE research and development method, with validation instruments and student response questionnaires. Data analysis involved expert judgment, percentage of questionnaire results, and one-group pretest posttest design. The results of the study are expected to contribute to improving the understanding of grade III Inclusive students on the theme of growth and development of living things through digital flipbook-based learning media.Keywords: Digital Flipbook, Media, Integrated Thematic Learning